2019
DOI: 10.1002/ece3.5382
|View full text |Cite
|
Sign up to set email alerts
|

Taking insight into the gut microbiota of three spider species: No characteristic symbiont was found corresponding to the special feeding style of spiders

Abstract: Microorganisms in insect guts have been recognized as having a great impact on their hosts' nutrition, health, and behavior. Spiders are important natural enemies of pests, and the composition of the gut microbiota of spiders remains unclear. Will the bacterial taxa in spiders be same as the bacterial taxa in insects, and what are the potential functions of the gut bacteria in spiders? To gain insight into the composition of the gut bacteria in spiders and their potential function, we collected three spider sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 75 publications
5
28
0
Order By: Relevance
“…The high abundance of representatives of the phylum Proteobacteria in the spiders' gut is in line with previous studies of other arthropods (Hu et al, 2019;Chen et al, 2016;Ruokolainen et al, 2016;Hammer et al, 2017). The genera, Acinetobacter and Pseudomonas were known for their role in energy, lipid metabolism and degradation of organophosphate based insecticides (Engel & Morgan, 2013;Van Dexter & Boopathy, 2019;Itoh et al, 2018) as reported earlier in other insects like weevils , Cerambycidae (Delalibera et al, 2005), and silkmoth (Anand et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The high abundance of representatives of the phylum Proteobacteria in the spiders' gut is in line with previous studies of other arthropods (Hu et al, 2019;Chen et al, 2016;Ruokolainen et al, 2016;Hammer et al, 2017). The genera, Acinetobacter and Pseudomonas were known for their role in energy, lipid metabolism and degradation of organophosphate based insecticides (Engel & Morgan, 2013;Van Dexter & Boopathy, 2019;Itoh et al, 2018) as reported earlier in other insects like weevils , Cerambycidae (Delalibera et al, 2005), and silkmoth (Anand et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…However, the gut bacterial diversity of this most diverse group is poorly explored. Till date, gut bacterial diversity of only six spider species (Pardosa laura , Pardosa astrigera , Nurscia albofasciata , Rabidosa rabida , Badumna longinqua , andArgiope bruennichi are known (Kennedy et al, 2020;Hu et al, 2019;Rivera et al, 2017;Sheffer et al, 2020). Kennedy et al, studied the impact of different food on the gut microbiome of the spider species Badumna longinqua , and observed that the gut bacterial diversity of this spider is generally diet-driven.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 0 dpe, the main components were Acinetobacter and Sphingomonas . Acinetobacter is an important part of the gut microbiota of many insects and has been found in the gut microbiota of Pardosa laura , Pardosa astrigera , Nurscia albofasciata , Omphisa fuscidentalis and other insects ( Liu et al, 2016 ; Hu et al, 2019 ). Acinetobacter assists the host in digesting food and converting nitrogen ( Briones-Roblero et al, 2016 ) and is an important insect gut probiotic.…”
Section: Discussionmentioning
confidence: 99%
“…With 16S/ITS1 rRNA gene a set of bacterial ( Thermus, Paracoccus , Sarcina , Neisseria , and Streptococcus ) and fungal ( Peniophoraceae , Malassezia , Alternaria , Neocucurbitaria , and Elsinoaceae ) taxa, at genus/family level, highly positively correlated with the high abundance of Xylella, was found. The genus Thermus can be found in many diverse habitats [ 63 ] including insects’ gut microbiome [ 64 ], and plants’ microbiome [ 65 ] with no specifically recognized function. Paracoccus genus includes species with plant growth-promoting traits [ 66 ].…”
Section: Discussionmentioning
confidence: 99%